ALEXITHYMIA, LONELINESS, AND SUICIDAL IDEATION AMONG ADOLESCENTS LIVING WITH HUMAN IMMUNODEFICIENCY VIRUS IN IMO STATE, NIGERIA - Uchegbu, Ifechi Cajethan; Ugokwe-Joseph, Rita; Ucheagwu, Valentine; Onwukwe, Leonard Chioma; Nnamdi, Chinenye Stephanie (African Journal of Social and Behavioural Sciences, 2025)
The study investigated the predictive role of the facets of alexithymia and loneliness on suicidal ideation among adolescents living with HIV in Imo State, Nigeria. Data were collected using a cross-sectional design from a sample of 328 HIV-positive participants (172(52.4%) females and 156(47.6%) males). While the hospitals used for the study were randomly selected, the participants were recruited using a convenience sampling technique. The participants’ ages ranged from 13 to 19 years, with a mean age of 15.97 years. Participants completed self-reported measures such as the Toronto Alexithymia Scale (TAS-20) by Bagby, Parker, and Taylor (1994); the Revised UCLA Loneliness Scale (Version 3) developed by Russell et al. (1980) and the Suicide Ideation Scale (SIS) by Rudd (1987). Four hypotheses were postulated and tested. Hierarchical multiple regression results showed that all the facets of alexithymia (difficulty identifying feelings, difficulty describing feelings, and external oriented thinking, and loneliness positively predicted suicidal ideation among adolescents living with HIV in Imo state, Nigeria. It is thus recommended that clinicians develop strategies aimed at improving emotional awareness and communication skills which can empower individuals to navigate and express their feelings while also creating a supportive environment for them to thrive.